1996
DOI: 10.1002/hep.510230621
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Epithelial Cadherin and α– and β–Catenins in Nontumoral Livers and Hepatocellular Carcinomas

Abstract: Expression of the cell adhesion molecule, epithelial nism. 2,3 The transmembrane linker glycoprotein that cadherin (E-CD) and its binding proteins, a-and b-caten-mediates this adhesion is thought to be epithelial cadins, in normal liver, chronic liver diseases, and hepato-herin (E-CD), the homophilic interaction of which links cellular carcinomas (HCCs) was investigated immuno-adjacent cells.4 E-CD is a member of the cadherin famhistologically. In normal liver, weak immunostaining of ily that is involved in Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
43
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 4 publications
8
43
1
1
Order By: Relevance
“…b-catenin protein accumulation was detected in 21 of 32 (66%) and 42 of 60 (70%) tumors by Western blot analysis (Figure 1b), and immunohistochemistry (Figure 2c), respectively, which was comparable with the results from previous studies (Ihara et al, 1996;Huang et al, 1999). Nuclear staining pattern of b-catenin was detected in six cases, with the rest showing strong staining in the cytoplasm and/or cytoplasmic membrane.…”
Section: Introduction Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…b-catenin protein accumulation was detected in 21 of 32 (66%) and 42 of 60 (70%) tumors by Western blot analysis (Figure 1b), and immunohistochemistry (Figure 2c), respectively, which was comparable with the results from previous studies (Ihara et al, 1996;Huang et al, 1999). Nuclear staining pattern of b-catenin was detected in six cases, with the rest showing strong staining in the cytoplasm and/or cytoplasmic membrane.…”
Section: Introduction Results and Discussionsupporting
confidence: 87%
“…Previous studies have shown that bcatenin is overexpressed in about 70% of HCC (Ihara et al, 1996;Huang et al, 1999), although only about 10-20% of these cases show b-catenin gene mutations (de La Coste et al, 1998;Miyoshi et al, 1998;Wong et al, 2001). Cyclin D1 gene amplification was reported in less than 15% of HCC patients (Zhang et al, 1993;Nishida et al, 1994), but overexpressions of cyclin D1 mRNA and cyclin D1 protein were reported in up to 22% (Nishida et al, 1994) and 58% (Joo et al, 2001) of HCC, respectively.…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25][26] For example, Charpin et al 21 reported that down-regulation of E-cad expression was noted in a majority of breast carcinomas; this significantly correlated with tumor grade and expression of p53, MIB-1 (growth fraction) and c-erbB2 in breast carcinomas. In the liver, Ihara et al 29 reported that thin trabecular and pseudoglandular HCC preserved or overexpressed E-cad, ␣-catenin, and ␤-catenin, whereas thick trabecular HCC frequently showed low E-cad, ␣-catenin, and ␤-catenin expression. They also reported that the E-cad, ␣-catenin, and ␤-catenin expression levels correlated with HCC differentiation grades.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the E-cad, ␣-catenin, and ␤-catenin expression levels correlated with HCC differentiation grades. 29 Kozyraki et al 32 reported that E-cad and ␣-catenin expression was frequently reduced or absent in HCC, and that alterations in cadherin expression in HCC correlated with large tumor size, low grade of histological differentiation, and occurrence of capsular and vascular invasion. The present study revealed for the first time that E-cad, ␣-catenin, and ␤-catenin expression was preserved (eu-regulation) or reduced (downregulation) relative to non-cancerous bile ducts in a majority of CC.…”
Section: Discussionmentioning
confidence: 99%